STUDYING THE “LEGAL FLOWS” AS A MULTIDISCIPLINARY METHOD TO PROMOTE CONSTITUTIONALISM AS A COMMON PROPERTY OF MANKIND - Michele Carducci; Anna Silvia Bruno (European Scientific Journal, ESJ, 2014)
This paper tackles the problems concerned the constitutional comparison, paying special attention to the “legal flows” in the Era of globalization of information and legal practices. With “legal flows” we mean the communicative interactions that occur between the legal operators from different parts of the world. These “flows” produce “imitations”, judicial dialogue, migrations of constitutional ideas, constitutional borrowing between various legal orders. The analysis of these dynamic phenomena requires two methodological needs: the transdisciplinarity opening to social history, to sociolinguistics and anthropology of communication; and the knowledge of the ideological dimensions of geopolitics and geography in the globalized Era. The comparison of “legal flows” becomes a necessary tool for the contemporary education of each legal scholar, dealing him to be used to dialogue, to accept the “other”, to understand the difficulties of the comparison and the respect of the complexity of cultures. This is the only way to promote constitutionalism as common property of mankind.